Decisional needs and interventions for young women considering contraceptive options: an umbrella review - Marit Müller De Bortoli; Sienna Kantymir; Lissa Pacheco-Brousseau; Bente Dahl; Elisabeth Holm Hansen; Krystina B. Lewis; Qian Zhang; Victoria Cole; Thomas Westergren; Dawn Stacey (BMC, 2024)
Abstract Background Although women face a wide range of contraceptive options, globally, young women are at risk of unintended pregnancies. Our umbrella review aimed to determine the decisional needs of nulligravida women aged 11 to 30 considering contraceptive options and identify effective interventions to support their involvement in making decisions about contraceptive use. Methods We followed Joanna Briggs Institute methods for umbrella reviews, theoretically guided by the Ottawa Decision Support Framework. We searched six electronic databases. Two reviewers independently screened citations, extracted data, and appraised quality using AMSTAR2. We analysed findings descriptively. Results Of 124 citations, we identified 11 reviews of variable quality (critically low to moderate quality): Six reported decisional needs and 5 reported on interventions. Decisional needs of young women were: (a) information needs about contraceptive options (e.g., mechanism of actions, eligibility, administration, side effects); (b) unclear values (concerns about hormone use) and features of different options (based on their religious values); and (c) need for support and resources (support from society and need for privacy). Compared to controls, decision support interventions including patient decision aids and patient education material increased knowledge and improved discussion of options with their clinicians. Conclusion Young women making contraceptive decisions experience unmet decisional needs. Effective interventions such as patient decision aids and general patient education materials may address their decisional needs and enhance their level of participation in making contraception decisions. Implications and contribution to the field: Young women's decisional needs when considering contraceptive use are informational needs, unclear values (including religious influences), need for support and resources when facing this decision. Interventions, such as patient decision aid and patient education material can, address decisional needs by improving young women's knowledge about contraceptive options.